Discontent, suffering and symptom: a Lacanian diagnostic re-reading via animist perspectivism - Dunker, Christian Ingo Lenz (Tempo Social, 2011)
The objective of this article is to explore the notion of life form as a useful concept for recontextualizing psychoanalytic diagnosis, as inspired by the works of Jacques Lacan, within the framework of the metadiagnosis of modernity developed by social theories, especially those of a critical inclination. To justify the clinical and critical utility of the concept of life form, the text embarks on a re-description of the fundamental oppositions of psychoanalytic diagnosis (lack and excess, production and non-production, determination and indetermination) as derived from the spheres of desire, language and work respectively. This aim in mind, the text proposes a homology between psychoanalytic psychopathology and the notion of Amerindian perspectivism developed by Viveiros de Castro (2002), which assumes a double purpose in this work: (1) to respond to critiques of Lacanian structuralism in psychopathology; and (2) to justify the distinction between symptom, suffering and discontent.